Research and application of coal mine occupational disease emergency plan - HU Jinguo; KANG Xiangtao; GAO Lu; YI Hanhua; TANG Meng; WANG Ziyi (Meikuang Anquan, 2022)
In order to reduce the incidence of occupational disease accidents in coal mines, according to the characteristics of occupational disease accidents in coal mines, the study of occupational disease emergency plans was carried out, and the preparation of emergency plans could be divided into four links: disaster evaluation methods, emergency organization and management, emergency response procedures and preventive measures. Taking a mine in Guizhou Province as an example, the role and effectiveness of coal mine occupational disease emergency plans in the process of occupational disease prevention and rescue were discussed. The results show that disaster evaluation is the basis of emergency plans, emergency organization and management is the core of emergency plans, emergency response procedures are the main body of emergency plans, and preventive measures are the focus of emergency plans. Handling occupational accidents in coal mines in strict accordance with the emergency plan can reasonably improve the effectiveness of the emergency plan.